Caracterização magnética de uma liga Ni-Mn-Sn com memória de forma magnética - Brito, Michel Raimundo de (2021)
The solidification dynamics of magnetic Heusler alloy have an essential role in the mechanical, electrical, and magnetic properties of the system. We report here a systematic investigation of the structural features, magnetic properties and dynamic magnetic behavior of Ni50Mn37Sn13 Heusler alloy solidified with two distinct molds. In particular, we produced cylinders of NiMnSn Heusler alloy by using Ceramic and Metallic molds, which allow us to modify the solidification dynamics of the system without atmosphere control. The structural results show the apparent modification on the L21 phase, associated with the solidification dynamics parameter that is reflected in the magnetization dynamics properties. We go beyond from the quasi-static magnetic characterization and address the dynamic magnetic behavior through the magnetoimpedance effect. Our findings reveal interesting modifications, not just in the structural properties of the material, but also in the quasi-static and dynamic magnetic properties of the samples. The magnetic dynamics results show a strong dependence of the used mold, a consequence of the mediated by the solidification process. This analysis amplifies the spectrum of Ni50Mn37Sn13 Heusler alloys obtained using the induction furnace technique without a controlled atmosphere, placing such samples as interesting sensor elements in magnetic devices.